Evaluating the quality of research co-production: Research Quality Plus for Co-Production (RQ + 4 Co-Pro) - Robert K. D. McLean; Fred Carden; Alice B. Aiken; Rebecca Armstrong; Judy Bray; Christine E. Cassidy; Olivia Daub; Erica Di Ruggiero; Leslie A. Fierro; Michelle Gagnon; Alison M. Hutchinson; Roman Kislov; et al. (BMC, 2023)
Abstract Background Co-production is an umbrella term used to describe the process of generating knowledge through partnerships between researchers and those who will use or benefit from research. Multiple advantages of research co-production have been hypothesized, and in some cases documented, in both the academic and practice record. However, there are significant gaps in understanding how to evaluate the quality of co-production. This gap in rigorous evaluation undermines the potential of both co-production and co-producers. Methods This research tests the relevance and utility of a novel evaluation framework: Research Quality Plus for Co-Production (RQ + 4 Co-Pro). Following a co-production approach ourselves, our team collaborated to develop study objectives, questions, analysis, and results sharing strategies. We used a dyadic field-test design to execute RQ + 4 Co-Pro evaluations amongst 18 independently recruited subject matter experts. We used standardized reporting templates and qualitative interviews to collect data from field-test participants, and thematic assessment and deliberative dialogue for analysis. Main limitations include that field-test participation included only health research projects and health researchers and this will limit perspective included in the study, and, that our own co-production team does not include all potential perspectives that may add value to this work. Results The field test surfaced strong support for the relevance and utility of RQ + 4 Co-Pro as an evaluation approach and framework. Research participants shared opportunities for fine-tuning language and criteria within the prototype version, but also, for alternative uses and users of RQ + 4 Co-Pro. All research participants suggested RQ + 4 Co-Pro offered an opportunity for improving how co-production is evaluated and advanced. This facilitated our revision and publication herein of a field-tested RQ + 4 Co-Pro Framework and Assessment Instrument. Conclusion Evaluation is necessary for understanding and improving co-production, and, for ensuring co-production delivers on its promise of better health.. RQ + 4 Co-Pro provides a practical evaluation approach and framework that we invite co-producers and stewards of co-production-including the funders, publishers, and universities who increasingly encourage socially relevant research-to study, adapt, and apply.